Análise da causalidade e cointegração entre variáveis macroeconômicas e o Ibovespa - Silva, Fabiano Mello da (2012)
The aim of this work was to assess the causality relation among the set of macroeconomic variables, represented by interest and exchange rates, inflation and Industrial Production Index as proxy of the Gross Internal Product regarding São Paulo Stock Exchange Index (IBOVESPA). The period of analysis was between January 1995 and December 2010 with 192 observations for each variable. Johansen s tests through Estatistical Trace and Maximum Eigenvalue indicated that there is at least one cointegration vector. In the analysis of Granger Causality Tests by way of Error Correction, it was found that there was short-term causality between Consumer Price Index and IBOVESPA. Regarding long-term results of Granger Causality, it was showed behavior of long-term among the macroeconomic variables with IBOVESPA. The results of the long-term of normalized vector for the IBOVESPA variable showed that most of sign parameters of cointegration equation are in agreement with the one suggested by economic theory. In other words, there was a positive behavior regarding Gross Internal Product and a negative one regarding inflation and exchange rate (it was hoped a positive relation) regarding IBOVESPA, except Brazil interest rate, which was not significant with that index. The variable of IBOVESPA was explained in more than 90% by itself in the twelfth month, followed by country-risk with less than 5%.